Rapid whole‐brain myelin imaging with selective inversion recovery and compressed SENSE. Issue 3 (9th November 2022) - Wang, Ping; Sisco, Nicholas; Yoo, Wonsuk; Borazanci, Aimee; Karis, John; Dortch, Richard
Abstract : Purpose: Quantitative magnetization transfer (QMT) using selective inversion recovery (SIR) can quantify the macromolecular‐to‐free proton pool size ratio ( PSR ), which has been shown to relate closely with myelin content. Currently clinical applications of SIR have been hampered by long scan times. In this work, the acceleration of SIR‐QMT using CS‐SENSE (compressed sensing SENSE) was systematically studied. Theory and Methods: Phantoms of varied concentrations of bovine serum albumin and human scans were first conducted to evaluate the SNR, precision of SIR‐QMT parameters, and scan time. Based on these results, an optimized CS‐SENSE factor of 8 was determined and the test–retest repeatability was further investigated. Results: A whole‐brain SIR imaging of 6 min can be achieved. Bland–Altman analyses indicated excellent agreement between the test and retest sessions with a difference in mean PSR of 0.06% (and a difference in mean R1f of −0.001 s −1 ). In addition, the assessment of the intraclass correlation coefficient (ICC) revealed high reliability in nearly all the white matter and gray matter regions. In white matter regions, the ICC was 0.93 (95% confidence interval [CI]: 0.88–0.96, p < 0.001) for PSR, and 0.90 (95% CI: 0.83–0.94, p < 0.001) for R1f . In gray matter, ICC was 0.84 (95% CI: 0.66–0.93, p < 0.001) in PSR, and 0.98 (95% CI: 0.95–0.99, p < 0.001) for R1f . The method also showed excellent capability to detect focal lesions in multiple sclerosis. Conclusion: Rapid, reliable, and sensitive whole‐brain SIR imaging can be achieved using CS‐SENSE, which is expected to significantly promote widespread clinical translation.